2012
DOI: 10.1186/1687-6180-2012-49
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the modified S-transform for time-frequency synchrony analysis and source localisation

Abstract: This article considers the problem of phase synchrony and coherence analysis using a modified version of the Stransform, referred to here as the Modified S-transform (MST). This is a novel and important time-frequency approach to study the phase coupling between two or more different spatially recorded entities with nonstationary characteristics. The basic method includes a cross-spectral analysis to study the phase synchrony of nonstationary signals, and relies on some properties of the MST, such as phase pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 47 publications
0
69
0
Order By: Relevance
“…5. It can be observed that proposed S-Transform (22) gives better localization when compared with Modified STransform [12].…”
Section: Simulation Results and Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…5. It can be observed that proposed S-Transform (22) gives better localization when compared with Modified STransform [12].…”
Section: Simulation Results and Discussionmentioning
confidence: 91%
“…4. It can be observed that small sign of indication for abrupt variation in proposed S-Transform (22) but it was not found in Modified S-Transform [12]. ii) Case at τ=1.054ms…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations